Pendampingan Edukasi Keuangan bagi Peserta Didik SMP Isen Mulang Palangka Raya - Aprilita, Aprilita; Widyaningsih, Dhina Sri; Bancin, John Budiman; Sukmani, Meylinda; Damayanti, Nurlia Eka; Nugroho, Sanjayanto (Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
Community Service Activities (PKM) with the theme financial education aim to build a culture of financial literacy among Isen Mulang Palangka Raya Middle School students. PKM activities were initiated and implemented by lecturers and students from the Faculty of Economics and Business, Palangka Raya University. There were 16 students who attended this educational activity consisting of 6 class VII students, 3 class VIII students, and 7 class IX students. Student enthusiasm is very high. This is demonstrated by the high level of interaction between students and presenters as well as responses from written questionnaires distributed by the Team at the end of the activity. There are 7 questions related to financial management asked by students to the presenters as well as 12 quizzes from the presenters which the students are able to answer.